A Study on the Fight Against Femtraffic Using the Femvertising Approach - Tanrıverdi, Ayşe Betül (Fırat University, 2026)
The research aimed to highlight the powerful images of women in traffic, using the femvertising pattern. Aggressive-masculine images in the automobile image were criticised, and powerful and feminine images were highlighted using the femvertising approach. The theoretical framework is based on postmodern feminist theory; the sample group consists of the Porsche Taycan car commercial and female drivers. The commercial was examined cross-sectionally in terms of its visuals, language, and spatial context; data was then collected from female drivers through semi-structured interviews. Thematic analysis was conducted using the techniques of Braun and Clarke and Coutés. The findings criticise gender stereotypes regarding women in traffic and reveal that women are better drivers than men. It can be said that women struggle with men in traffic in their daily lives and in the media. Male drivers make women feel unsafe in traffic; they legitimise their own risky behaviour. The aggressive hegemonic structure of traffic is one of the factors that leads women to prefer safe cars. The car has a comprehensive feminist value of freedom for women. Femtraffic has been put forward for the strong representation of women in traffic. Raising social awareness against discrimination against women in traffic and increasing academic and institutional studies are important for the femtraffic movement.

Araştırmada trafikteki kadınların güçlü imajlarının ön plana çıkarılması hedeflenmiş, femvertising desen kullanılmıştır. Otomobil imgesindeki agresif-eril erkeksi imajlar eleştirilmiş, femvertising yaklaşımla güçlü ve feminen imajlar öne çıkarılmıştır. Teorik çerçeve postmodern feminist kurama dayanmakta; örnek grubunu Porshe Taycan otomobil reklam filmi ve kadın sürücüler oluşturmaktadır. Reklam filmi görsellik, üretilen dil, mekan bağlamlarıyla kesitsel olarak incelenmiş; ardından kadın sürücülerden yarı yapılandırılmış mülakatla veri toplanmıştır. Tematik analizin yapıldığı çalışmada Braun ve Clarke ile Coutés’ın teknikleri kullanılmıştır. Bulgularda trafikteki kadına yönelik toplumsal cinsiyet yargıları eleştirilmekte; kadınların erkeklerden daha iyi araç kullandığı görülmektedir. Kadınların gündelik yaşamlarında ve medyada trafikteki erkeklerle mücadele ettikleri söylenebilir. Erkek sürücüler trafikteki kadınlara kendilerini güvensiz hissettirmekte; kendi riskli davranışlarına meşru zemin oluşturmaktalardır. Trafiğin agresif hegemonik yapısı kadınlara güvenli otomobili tercih ettiren unsurlardandır. Otomobilin kadınlar için özgürlük kapsamlı feminist değeri vardır. Trafikte kadının güçlü temsili için femtrafik kavramı öne sürülmüştür. Trafikte kadına yönelik ayrımcılığa karşı toplumsal farkındalığın geliştirilmesi, akademik ve kurumsal çalışmaların artırılması femtrafik hareket için önemlidir.
Femvertising Yaklaşımla Femtrafik Mücadelesi Üzerine Bir İnceleme
Keywords: Women's Studies; Kadın Araştırmaları